Applications of indocyanine green based near-infrared fluorescence imaging in thoracic surgery - Zhou, Jian (J Thorac Dis, 2016)
Near-infrared (NIR) fluorescence guided surgery is an emerging technique. This technique uses the combination of dyes and NIR imaging devices to expand the visible spectrum. Thus it can provide more anatomic and functional information, and may facilitate a more complete resection of cancer, or better protection of important normal structures. Recently, significant progress has been made in the field of NIR fluorescence guided thoracic surgery. This may lead to better prognosis and health-economic outcomes. In this article, the current studies of indocyanine green (ICG) based NIR fluorescence guided thoracic surgeries are reviewed. The applications are classified into four categories, which are applications based on blood supply, lymphatic drainage, the enhanced permeability and retention (EPR) effect, and the other mechanisms.